AN INTERSECTIONAL ANALYSIS OF GENDERED PRECARITY IN MIGRATION AND STATELESSNESS - Cassadee Orinthia Yan (PEOPLE: International Journal of Social Sciences, 2025)
This article presents an intersectional view of how gender influences the joint production of migration and statelessness, leading to different types of precarity that cannot be understood through any of the single axes—legal status, nationality, or gender—only. Based on Crenshaw’s definition of intersectionality and critical feminist citizenship literature, the confrontation regards statelessness as an unexclusive legal flaw but an empowered position within the overlapping regimes: patriarchal nationality laws that limit the intergenerational passing of citizenship; migration regulations that make the movement and providing protection dependent on employer sponsorship, family status, or heteronormative recognition; and political economies that direct women migrants to informal or care work. These regimes together produce three interrelated mechanisms: (a) legal discontinuity, where female and non-binary migrants get lost between family law, citizenship statutes, and asylum systems; (b) administrative opacity, where red tape and recognition criteria of one’s identity (for instance, name, marital, or gender markers) convert official rights into practical exclusion; and (c) economic subordination, where unstable jobs and limited access to services render legal actions virtually impossible. The paper combines doctrinal analysis of nationality and asylum frameworks in the context of case-based evidence on groups made stateless or "functionally stateless" in migration, such as minority women displaced across borders and transgender asylum seekers facing documentation mismatch. The argument goes in three stages: first, it demonstrates how gendered norms are integrated into citizenship transmission and identity recognition; second, it follows the trail of migration controls that boost those norms at borders, in camps, and in labor markets; finally, it shows how economic dependence and violence risk giving rise to legal non-recognition, thus creating intergenerational exclusion. The contribution is twofold: conceptually, it delineates intersectional precarity as a set of mechanisms rather than a descriptive label; normatively, it shifts the focus of reform from the mere granting of status to the transformation of the gendered rules of recognition- birth registration, gender and parentage markers, and access to work and justice- without which formal nationality cannot guarantee substantive belonging.